A prospective comparison of postoperative pain and quality of life in robotic assisted vs conventional laparoscopic gynecologic surgery - Zechmeister, Jenna R.; Pua, Tarah L.; Boyd, Leslie R.; Blank, Stephanie V.; Curtin, John P.; Pothuri, Bhavana (American journal of obstetrics and gynecology, 2015)
We sought to compare robotic vs laparoscopic surgery in regards to patient reported postoperative pain and quality of life. This was a prospective study of patients who presented for treatment of a new gynecologic disease requiring minimally invasive surgical intervention. All subjects were asked to take the validated Brief Pain Inventory-Short Form at 3 time points to assess pain and its effect on quality of life. Statistical analyses were performed using Pearson x2 and Student’s t test. One hundred eleven were included in the analysis of which 56 patients underwent robotic assisted surgery and 55 patients underwent laparoscopic surgery. There was no difference in postoperative pain between conventional laparoscopy and robotic assisted surgery for gynecologic procedures. There was a statistically significant difference found at the delayed postoperative period when evaluating interference of sleep, favoring laparoscopy (ROB 2.0 vs LSC 1.0; P = .03). There were no differences found between the robotic and laparoscopic groups of patients receiving narcotics (56 vs 53, P = .24, respectively), route of administration of narcotics (47 vs 45, P > .99, respectively), or administration of nonsteroidal antiinflammatory medications (27 vs 21, P = .33, respectively). Our results demonstrate no difference in postoperative pain between conventional laparoscopy and robotic assisted surgery for gynecologic procedures. Furthermore, pain did not appear to interfere consistently with any daily activity of living. Interference of sleep needs to be further evaluated after controlling for bilateral salpingo-oophorectomy.